TEACHING ENGLISH THROUGH BASED BRAIN STRATEGY TO YOUNG LEARNER - Nina Khayatul Virdyna, M.Pd; Evha Nazalatus Sy, M. Pd (The Ellite of Unira, 2021)
English has a need for some people around the world. People been struggling to learn and master English actively. And so teachers around the world been struggling to find the best way to teach the students of how to master English well. Not many people realize that the ability to speak and to master new language is an innate ability. Its in the brain. When the teacher are able to dig thebrain potential of the students than all the problem of learning English suffered by the students are solved. In this article, the author will show what our brains do when students listen to you. Most particularly, we will show how the brains of infants and children are tuned to understand language, and how changes in the brain during development serve as preconditions for language learning. Understanding language is a process that involves at least two important brain regions, which need to work together in order to make it happen. This would be impossible without connections that allow these brain regions to exchange information. The nerve fibers that make up these connections develop and change during infancy and childhood and provide a growing underpinning for the ability to understand and use language. We will show you how to gain students’ brain potentiality. So, they can learn English maximally like their own language